2008
DOI: 10.1534/genetics.108.095893
|View full text |Cite
|
Sign up to set email alerts
|

A and C Genome Distinction and Chromosome Identification inBrassica napusby Sequential Fluorescencein SituHybridization and Genomicin SituHybridization

Abstract: The two genomes (A and C) of the allopolyploid Brassica napus have been clearly distinguished using genomic in situ hybridization (GISH) despite the fact that the two extant diploids, B. rapa (A, n ¼ 10) and B. oleracea (C, n ¼ 9), representing the progenitor genomes, are closely related. Using DNA from B. oleracea as the probe, with B. rapa DNA and the intergenic spacer of the B. oleracea 45S rDNA as the block, hybridization occurred on 9 of the 19 chromosome pairs along the majority of their length. The patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
63
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(69 citation statements)
references
References 43 publications
5
63
1
Order By: Relevance
“…It is not possible to identify specific Bgenome linkage groups using GISH with B. nigra genomic DNA, since the probe paints the centromeric area of any B-genome chromosome (Navabi et al 2010). To distinguish and visualize different B-genome chromosomes, one needs to use probes of BAC clones specific for a particular B-genome chromosome (Hasterok et al 2005;Howell et al 2008;Xiong et al 2010).…”
Section: Cytological Tracking Of the B-genome Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not possible to identify specific Bgenome linkage groups using GISH with B. nigra genomic DNA, since the probe paints the centromeric area of any B-genome chromosome (Navabi et al 2010). To distinguish and visualize different B-genome chromosomes, one needs to use probes of BAC clones specific for a particular B-genome chromosome (Hasterok et al 2005;Howell et al 2008;Xiong et al 2010).…”
Section: Cytological Tracking Of the B-genome Chromosomesmentioning
confidence: 99%
“…CR, cotyledon retention; MLD, margin leaf division; ILD, incision of leaf division; DTF, days to flowering; STC, stem color; FC, flower color; STL, stem length; NB, number of primary branches; SW, silique width; BL, beak length; DTM, days to maturity; SC, seed color. *significant at p , 0.01; **significant at p , 0.05. approach taken by Howell et al (2008) to detect the A7/C6 translocation in B. napus var. ''Westar.''…”
Section: Cytological Tracking Of the B-genome Chromosomesmentioning
confidence: 99%
“…Natural euploid B. napus displays predominantly 19 bivalents at Metaphase I (MI) and an almost strict disomic inheritance; this shows that the vast majority of COs are formed between homologous chromosomes. Evidence for rare homoeologous exchanges was obtained in several B. napus cultivars Sharpe et al, 1995;Lombard and Delourme, 2001;Osborn et al, 2003;Piquemal et al, 2005;Udall et al, 2005;Howell et al, 2008), but their frequency remains very low compared with the rate in resynthesized B. napus Sharpe et al, 1995;Udall et al, 2005;Lukens et al, 2006;Gaeta et al, 2007;Szadkowski et al, 2010). Contrary to wheat, comparisons of meiosis among B. napus allohaploid plants, which carry one copy of each of the 10 A and 9 C B. napus chromosomes (AC), showed that allohaploids produced from some varieties displayed only a few univalents (i.e., chromosomes that fail to form a CO), whereas those produced from other varieties displayed mostly univalents (Olsson and Hagberg, 1955;Renard and Dosba, 1980;Attia and Rö bbelen, 1986;Jenczewski et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The first improvement is the application of chromosome-specific bacterial artificial chromosome (BAC) probes and new repetitive sequences, which has facilitated chromosome identification in B. rapa and B. oleracea (Howell et al 2002(Howell et al , 2008Koo et al 2004;Lim et al 2005Lim et al , 2007Mun et al 2008;Feng et al 2009;Kim et al 2009). Howell et al (2002) made a first step toward integration of all nine linkage groups of the B. oleracea genetic map to the corresponding chromosomes using BACs as probes for FISH hybridization.…”
mentioning
confidence: 99%
“…Similarly, the genetic linkage map and the B. rapa cytogenetic map was integrated by BAC-FISH (Mun et al 2008;Kim et al 2009). The second improvement in B. napus cytogenetics is the ability to identify the C genome either by using a BAC clone containing a ubiquitous C-genome repeat (Alix et al 2008) or by using a modified GISH technique that uses a repetitive probe for blocking DNA (Howell et al 2008). The latter study not only identified the A and C genomes in B. napus, but also used a sequential procedure with FISH and GISH that allowed for direct visualization of a known reciprocal translocation (Howell et al 2005(Howell et al , 2008.…”
mentioning
confidence: 99%